Road testing new CAR design strategies in multiple myeloma - Rana, Priyanka S.; Murphy, Elena V.; Kort, Jeries; Driscoll, James J. (Frontiers in Immunology, 2022)
A deeper understanding of basic immunology principles and advances in bioengineering have accelerated the mass production of genetically-reprogrammed T cells as living drugs to treat human disease. Autologous and allogeneic cytotoxic T-cells are weaponized to express synthetic, chimeric antigen receptors (CAR) that specifically engage antigenic regions on tumor cells in an MHC-independent manner. While CAR-based therapies demonstrate robust, sustained responses in select patients, including those diagnosed with multiple myeloma (MM), many obstacles persist. Additional co-stimulatory signaling regions were added to second-generation CARs to promote IL-2 synthesis, activate T cells and avoid apoptosis. Third generation CARs are composed of two different co-stimulatory signaling units along with the CD3ζ or FcεRIγ signaling domain. Typically, CAR T-cells incorporate a potent constitutive promoter that maximizes long-term CAR expression but recent evidence suggests that constitutive CAR activation promotes T-cell exhaustion. Hypoxia-inducible elements conditionally drive CAR expression to target proliferating MM cells in the bone marrow tumor microenvironment. CAR T-cell proliferation and persistence may also be achieved by optimizing co-stimulatory signals and by blocking intrinsic regulators of T-cell inactivation. TRUCKs (T-cells Redirected for Universal Cytokine Killing) are fourth generation CAR T-cells that, upon binding a specific tumor antigen, produce cytokines intended to recruit endogenous immune cells. Suicide genes engineered into CAR T-cells is prudent given the potential for long term “on-target, off-tumor” effects on healthy cells. Universal allo-CAR T-cells represent a portable, off-the-shelf source for large scale applications, while multi-target CAR T-cells may improve antigen recognition and reduce antigen escape. Logic-gated CAR T-cells recognize tumor-specific molecular features that are coupled with Boolean-generated binary gates to dictate cell-fate decisions. CAR T-cells offer to revitalize the immune system and reimagine the treatment of cancer, autoimmune and infectious disease.